TINJAUAN YURIDIS TERHADAP MEKANISME PENYERAHAN SEBAGIAN PELAKSANAAN PEKERJAAN KEPADA PERUSAHAAN LAIN (OUTSOURCHING) STUDI KASUS DI PT. SYABILLA RIZKY ABADI DAN CV. RIMAS AYU SAMARINDA - Jemain jemain (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACT Mechanism of outsourcing labor relations there are three requirements that must be met, namely : 1. Conditions Material, namely : done separately from the main activity; Performed with direct or indirect orders from employers; an auxiliary enterprise as a whole; and does not directly inhibit the production process. 2. Conditions Formal, namely : the company must be a legal entity; must obtain permission from the operational agencies responsible for labor affairs at the Department of Labor local outsourcing company which is located. 3. Conditions Substantially, the terms of employment are generally in the form of normative provisions and working conditions imposed on the employer company.Outsourcing as a labor supply by others performed by first separating the main job (core business) with auxiliary enterprises (non-core) in a written document prepared by the management company. In doing outsourcing company outsourcing service users in collaboration with outsourcing companies, where the legal relationship embodied in a cooperation agreement that includes, among others, about the term of the agreement as well as any areas of cooperation which is a form of outsourcing. Employee signed an agreement with outsourcing outsourcing company outsourcing the user to be placed in the company.As a result of the law in terms of labor delivery to third parties (outsourcing) in terms of material and formal requirements are not met, then the result will be null and void, the existing employment relationship switched from employment or employment agreement between workers/laborers with the recipient company chartering jobs/employment services provider/labor into employment or employment agreement between workers/laborers with labor service user companies/workers. In this case workers/laborers can apply to the determination of the Industrial Dispute Settlement agencies. Employee outsourcing for the service user is placed in the company outsourcing the work shall comply with the applicable provisions of the outsourcing companies in the agreement. Dispute resolution labor issues resolved internally between companies outsourcing services outsourcing to corporate users, it can also be done by holding a meeting with the workers/laborers to discuss labor issues that occur in the implementation of outsourcing.Settlement disputes between workers/laborers with industrial outsourching outsourching be the sole responsibility outsourching enterprise itself. employment problems arising between enterprises with enterprise outsourching outsourching service users, diselesaiakan internally by the enterprise service users outsourching outsourching enterprises, it is also possible to have a meeting with the employee/labor to discuss the problems of employment that occurred in the execution outsourching.